CARDIORESPIRATORY FITNESS IN OBESE AND NON-OBESE CHILDREN. (CIPEEX, 2023)
Childhood obesity is considered by the World Health Organization (WHO) as a pandemic. One of the ways to assess childhood obesity is by calculating the body mass index (BMI) and waist circumference (WC). It is known that with the advent of screen use and reduced physical activity, children tend to become obese and experience a decrease in their cardiorespiratory fitness (CRF). Therefore, the objective of this work is to associate abdominal fat with the cardiorespiratory fitness (CRF) of schoolchildren. This is a cross-sectional observational study. Obese and non-obese children aged 4-13 years were included, with parental/guardian consent for participation in the study. Children with factors that prevent the performance of the cardiorespiratory fitness test (amputations, osteomyoarticular problems) were excluded. The children underwent the collection of anthropometric measurements (mass, height, BMI, and waist circumference) followed by the assessment of cardiorespiratory fitness through the six-minute walk/run test. The study included 110 children, 57 (51.8%) boys and 53 (48.2%) girls. There was no association between the classification of obesity and ACR (p=0.284). Non-obese children covered a greater distance (735.84±102.0m) compared to (685.61±112.7m) in the obese group (p= 0.016). Due to the aforementioned facts, it was possible to analyze that ACR is reduced in obese schoolchildren, making the monitoring of these groups extremely relevant for the improvement of pediatric health.
Keywords: Childhood Obesity; Cardiorespiratory Fitness; Pediatrics